SARS, MERS and other Viral Lung Infections - Hui, David; Rossi, Giovanni; Johnston, Sebastian (ERS Monograph, 2016)
Viral respiratory tract infections are important and common causes of morbidity and mortality worldwide. In the past two decades, several novel viral respiratory infections have emerged with epidemic potential that threaten global health security. This Monograph aims to provide an up-to-date and comprehensive overview of severe acute respiratory syndrome, Middle East respiratory syndrome and other viral respiratory infections, including seasonal influenza, avian influenza, respiratory syncytial virus and human rhinovirus, through six chapters written by authoritative experts from around the globe.